ANALISIS EFISIENSI HUKUM EKONOMI DALAM MENDORONG PERTUMBUHAN EKONOMI: STUDI KAJIAN PUSTAKA - Tehedi Tehedi; Dinda Ayu Izmi (JEBIMAN : Jurnal Ekonomi, Bisnis, Managemen dan Akuntansi, 2025)
This study aims to analyse the efficiency of economic law in promoting economic growth through a literature review approach. Economic law efficiency is seen as a key factor in creating a conducive investment climate, reducing transaction costs, and providing legal certainty and protection for business actors. Using a literature review method and a normative legal approach, this study examines various relevant literature, theories, and previous research findings. The analysis reveals that the application of efficiency principles in economic law, such as effective contract enforcement and property rights protection, significantly contributes to sustainable economic growth. However, challenges such as overlapping regulations, bureaucracy, and weak law enforcement remain obstacles to optimising the role of economic law in Indonesia. Therefore, regulatory reform and strengthening law enforcement are needed so that economic law efficiency can function optimally as a driver of national economic growth.